The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1289/ehp8507
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Lead (Pb) Exposure and Peripheral Blood DNA Methylation (5mC) and Hydroxymethylation (5hmC) in Mexican Adolescents from the ELEMENT Birth Cohort

Abstract: Background: Gestational lead (Pb) exposure can adversely affect offspring health through multiple mechanisms, including epigenomic alterations via DNA methylation (5mC) and hydroxymethylation (5hmC), an intermediate in oxidative demethylation. Most current methods do not distinguish between 5mC and 5hmC, limiting insights into their individual roles. Objective: Our study sought to identify the association of trimester-specific (T1, T2, T3) prenatal Pb exposure with 5mC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 74 publications
(80 reference statements)
1
19
0
Order By: Relevance
“…For example, DNA methylation at promoters is generally associated with repression of genes, while intragenic DNA methylation is associated with gene activation [ 53 , 54 ]. The 5-hydroxymethylcytosine (5hmC) modification plays a critical role post-fertilization and in primordial germ cells (PGCs) during the dynamic reprogramming of DNA methylation [ 55 - 57 ] but has also been shown to be a stable epigenetic mark present in a variety of mammalian tissues [ 58 - 60 ], and we have shown that it is stably reprogrammed by perinatal exposures in mice and humans [ 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, DNA methylation at promoters is generally associated with repression of genes, while intragenic DNA methylation is associated with gene activation [ 53 , 54 ]. The 5-hydroxymethylcytosine (5hmC) modification plays a critical role post-fertilization and in primordial germ cells (PGCs) during the dynamic reprogramming of DNA methylation [ 55 - 57 ] but has also been shown to be a stable epigenetic mark present in a variety of mammalian tissues [ 58 - 60 ], and we have shown that it is stably reprogrammed by perinatal exposures in mice and humans [ 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human studies investigating the effects of developmental Pb exposure on the epigenome have focused primarily on the measurement of Pb in maternal blood, maternal tibia or patella, cord blood, or neonatal blood spots as proxies for Pb exposure during pregnancy. These studies have repeatedly demonstrated that Pb exposure is associated with changes in DNA methylation and hydroxymethylation in offspring blood [ 62 , 124 - 126 ], and sex differences have been reported [ 125 - 127 ]. Moreover, recent work suggests that maternal Pb-induced changes in DNA methylation may be transmitted to grandchildren [ 128 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous recent studies have highlighted the critical role for DNA hydroxymethylation in the context of environmental exposures and disease. DNA hydroxymethylation entails the oxidative conversion of 5-methylcytosine to 5-hydroxymethylcytosine by TET dioxygenases. , While 5-hydroxymethylcytosine is an intermediate in the process of active DNA demethylation, it is also now considered to be a stable epigenetic modification and is associated with regulation of gene expression and alternative splicing. TET dioxygenases convert 5-methylcytosine to 5-hydroxymethylcytosine using iron (Fe II), α-ketoglutarate, and vitamin C as cofactors, and can also catalyze the further oxidation of 5-hydroxymethylcytosine to 5-formylcytosine and 5-carboxylcytosine. , Like 5-hydroxymethylcytosine, 5-formylcytosine and 5-carboxylcytosine are intermediates in the process of demethylation of DNA through both replication-dependent dilution as well as pathways involving DNA repair enzymes such as thymine DNA glycosylase. , Three TET dioxygenases, TET1, TET2, and TET3 have been identified and each show distinct expression patterns during normal development and in differentiated tissues. , TETs are most highly expressed in embryonic stem cells and during early development, where they function in active DNA demethylation during both waves of reprogramming. 5-Hydroxymethylcytosine is present to a notable degree in embryonic stem cells and the brain. The specific role of 5-hydroxymethylcytosine in the brain is only beginning to be characterized, but there is evidence to suggest it plays a role in neurodevelopment and aging, and its aberrant expression is implicated in several neurological disorders. , Furthermore, 5-hydroxymethylcytosine is influenced by the environment, with exposures such as arsenic, lead, and pesticides associated with alterations in 5-hydroxymethylcytosine in the brain and blood. ,, Future studies will undoubtedly continue to clarify the role for 5-hydroxymethylcytosine in normal neurodevelopment, environmental health, and disease.…”
Section: Background: Types Of Epigenetic Informationmentioning
confidence: 99%
“…48,49 Furthermore, 5-hydroxymethylcytosine is influenced by the environment, with exposures such as arsenic, lead, and pesticides associated with alterations in 5-hydroxymethylcytosine in the brain and blood. 8,34,50 Future studies will undoubtedly continue to clarify the role for 5-hydroxymethylcytosine in normal neurodevelopment, environmental health, and disease. Programming of DNA Methylation and Hydroxymethylation During Development.…”
Section: Informationmentioning
confidence: 99%
“…5'-Methylcytosine (5mC) is the main form of DNA methylation and one of the earliest and most thoroughly studied epigenetic regulatory mechanisms, playing an important role in cancer, gene expression, aging, atherosclerosis, Alzheimer's disease and other diseases [15][16][17]. Studies have shown that the increased expression of hTERT in colorectal cancer and gastric cancer was associated with the degree of hypermethylation of the hTERT gene, which seriously affected recurrence after treatment [18,19].…”
Section: Introductionmentioning
confidence: 99%